Knowledge, attitudes, and practices of polio vaccination among mothers attending vaccination sites in Gaza during the conflict - El Bilbeisi, Abdel Hamid; El Afifi, Amany; Abuzerr, Samer; Alwahedy, Isra Kanan; Alwahedy, Saja Kanan (Frontiers in Pediatrics, 2025)
ObjectiveThis study aims to evaluate the knowledge, attitudes, and practices (KAP) related to polio vaccination among mothers attending vaccination sites in Gaza during the ongoing conflict.MethodsA cross-sectional survey was conducted from 1 to 12 September, 2024, targeting a representative sample of 474 mothers from ten primary healthcare centers across the governorates of Gaza. Participants were randomly selected using a cluster sampling method. Data on socio-demographics and KAP towards polio vaccination were collected through a validated, interview-based questionnaire. Statistical analysis was performed using SPSS version 26.ResultsOf the 474 mothers surveyed, 44.7% were between 26 and 30 years old. Around 35.4% had a primary-level education, 48.1% were employed, 48.5% had two to three children, and 49.4% had children aged between one day and less than twelve months. The majority of mothers exhibited good knowledge (85.7%), positive attitudes (86.1%), and good practices (67.1%) regarding childhood vaccination. Knowledge scores were significantly associated with the mother's age, number of children, and the children's age. Attitude scores were significantly related to the mother's age and number of children (P < 0.05 for all). However, no significant relationship was observed between socio-demographic factors and practice scores.ConclusionMost mothers demonstrated good knowledge and positive attitudes towards polio vaccination, although only about two-thirds reported good vaccination practices. Younger mothers and those with younger children had better knowledge, while middle-aged mothers expressed more positive attitudes. Importantly, socio-demographic factors were not linked to practice levels. The relatively low adherence to vaccination practices requires further attention.